Cakupan Pelayanan Halte Trans Metro Bandung dan Trans Metro Pasundan Terhadap Guna Lahan Permukiman di Kota Bandung - Achmad Fauzan Iscahyono; Habibi Mujahidin Mukhlis Sudrajat (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2026)
The less-than-ideal condition of bus stops in Bandung City has the potential to hinder the movement of people in residential areas that depend on buses, as well as reduce the advantages of public transportation as a sustainable mobility solution. This study aims to identify the service coverage of Trans Metro Bandung (TMB) and Trans Metro Pasundan (TMP) bus shelters in relation to residential land use in Bandung City. The method used is quantitative research with buffer and network analysis utilizing ArcGIS 10.8 software. The data collected includes the distribution points of bus shelters, road networks, and residential land use in Bandung City. The buffer analysis results show that the service coverage of bus shelters within a 400-meter radius largely fails to serve most of the residential land use adequately. Furthermore, the network analysis indicates that although some residential areas fall within the service radius, accessibility remains limited due to the condition of road networks that are still not accessible and adequate. The conclusion of this study is that many residential land areas are still underserved and inaccessible to TMB and TMP bus shelters. Therefore, additional bus shelters, feeder routes, and road infrastructure improvements are needed to enhance the accessibility and service coverage of TMB and TMP bus transportation in Bandung City.